The electric transport properties of iridate Sr2-xBixIrO4 and Sr2-yDyyIrO4. Issue 1 (1st November 2022) - Xiong, Yanfei; Zu, Hao; Liu, Hui
Abstract : Sr2 IrO4 is predicted to be a new superconductor in theory, and its electric transport properties have attracted much attention in the field of physics. Here we prepared a series of polycrystalline samples doped with Sr2-x Bix IrO4 (x=0, 0.02, 0.04, 0.06, 0.08) and Sr2-y Dyy IrO4 (y=0, 0.02, 0.04, 0.06) respectively. The influence of the two ions on the lattice structure and electronic structure after the substitution of the Ir site is very similar, which makes the overall reduction trend of IrO6 octahedron and Ir-O1-Ir bond angle. The resistivity shows a non-monotonic change with doping and still maintains the insulation. The low-temperature section, medium-temperature section, and high-temperature section conform to three-dimensional variable range hopping (3D-VRH), thermal activation model, two-dimensional weak localization model respectively.